Materials On Early Childhood Education In The Family Based On Local Wisdom (Belief In Ancestors) - Ali, Musyafa; Husnifah, Hikmatul; Nurhayati, Ismi (International Proceedings of Nusantara Raya, 2022)
As the first educational institution, the family has an important role in the educational process, and the preservation of local wisdom to the child as the next generation. This study aims to describe and analyze early childhood education materials in families based on local wisdom (belief in ancestors). This research was conducted on the Aboge community in Cikakak Village, Banyumas Regency. This research is a field research, using qualitative methods. Data are obtained through observation, interviews and documentation. The analysis is carried out by means of reduction, presentation and verification as well as drawing conclusions. The results of this study show the material taught by parents, which includes material on godliness, humanity, art, appearance, experience, trust and nobleness. These materials are taught by parents and elders (people who are aged in the region) either orally or in direct practice, besides that parents also involve children in various activities both religious and civilized.